2023
DOI: 10.1021/acsami.2c16710
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Particles Retain Their Structure and Function while Passing through the Gastrointestinal Tracts of Mice and Humans

Abstract: Mesoporous silica particles (MSPs) can be used as food additives, clinically for therapeutic applications, or as oral delivery vehicles. It has also been discussed to be used for a number of novel applications including treatment for diabetes and obesity. However, a major question for their possible usage has been if these particles persist structurally and retain their effect when passing through the gastrointestinal tract (GIT). A substantial breaking down of the particles could reduce function and be clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Meso- and macroporous , siliceous materials have been studied extensively for use in diverse applications for over 20 years. They show promise in areas as diverse as heterogeneous catalysis, , energy storage, adsorption and separations, and biomedical devices. These siliceous materials are synthesized in a wide range of morphologies and by several processes to meet the diverse physical and chemical requirements of these applications. Common materials include composites, ,, aerogels and xerogels, ,,, films and membranes, , particles, and microstructured monoliths. , Preparation methods include sol–gel processing, ,, templating methods, ,,,,, deposition, and a variety of other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Meso- and macroporous , siliceous materials have been studied extensively for use in diverse applications for over 20 years. They show promise in areas as diverse as heterogeneous catalysis, , energy storage, adsorption and separations, and biomedical devices. These siliceous materials are synthesized in a wide range of morphologies and by several processes to meet the diverse physical and chemical requirements of these applications. Common materials include composites, ,, aerogels and xerogels, ,,, films and membranes, , particles, and microstructured monoliths. , Preparation methods include sol–gel processing, ,, templating methods, ,,,,, deposition, and a variety of other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous silica particles (MSPs) such as SBA-15 are characterized by a large surface area, variable mesopore size (2–50 nm), pore volume, mesocrystalline order, and ease of functionalization. , These properties can be fine-tuned and are attractive for controlling molecular diffusion. The hydrodynamic dimensions of enzymes can be in the order of the pore size of MSPs, and nonobvious and diffusion-related effects may be expected. , In addition to these features of diffusion and molecular control, this type of silica is researched for use in drug delivery, biocatalysis, and as therapeutic agents. Recent research has also explored the potential of MSPs for therapeutic application and large-scale production. , …”
Section: Introductionmentioning
confidence: 99%
“…5−8 Recent research has also explored the potential of MSPs for therapeutic application and large-scale production. 9,10 Metabolic syndrome, which includes obesity and type 2 diabetes (T2D), is researched for its potential to be treated and prevented with MSPs. It was shown that amylase and lipase are adsorbed on MSPs in a pore-size-dependent manner both in vitro and ex vivo in gastric fluids.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations